The psychological influence of the diagnosis of breast cancer on therapeutic options selection - Răzvan V. Scăunaşu; Ștefan Voiculescu; Bogdan Popescu; Cristina Cozma; Radu Jecan; Cristian Bălălău (Journal of Mind and Medical Sciences, 2017)
The therapeutic management decision-making process for breast cancer is complex, and is influenced by multiple factors including patient age, comorbidities, ethnicity, education, and availability of immediate or delayed reconstruction options. Our study analysed 276 patients diagnosed with breast cancer in the “Colțea” Clinical Hospital between 2014 and 2015. Mean patients age was 61.24, median 62, with a range of 31 to 89 years. Younger age was associated with a less advanced local disease and younger patients were more likely to choose and benefit from conservative surgery. Most patients (61.76%) came from rural areas. Place of origin had a significant influence on the tumor size at the time of diagnosis (3.9 cm vs. 1.8cm) as well as on the choice of surgical procedure. Personalized treatment management plans that include aesthetic satisfaction coupled with oncological safety should be the objectives of contemporary breast surgery. Patient age is so important to the decision making process that it has been proposed as a determinant of educational and counselling strategies. From our experience, young patients from urban areas were more proactive patients. They were diagnosed earlier and more involved in treatment decisions compared with patients from rural areas, who generally did not question the surgeon’s opinion. Factors that influence the decision-making process likely include age, socioeconomic status, availability of radiotherapy, the necessity of periodic follow-up and the concern about recurrence.